PROVE-IT trial: economic analysis - de Portu, Simona; Montella, Sabato; Cammarota, Simona; Citarella, Anna; Mantovani, Lorenzo G. (Farmeconomia. Health economics and therapeutic pathways, 2008)
Introduction: the PROVE-IT (“Intensive versus moderate lipid lowering with statins after acute coronary syndromes”) was a comparison of pravastatin 40 mg/die versus atorvastatin 80 mg/die in patients with an acute coronary syndrome (ACS). Aim: our aim was to investigate the economic consequence of high dose of atorvastatin vs usual-dose of pravastatin in Italian patients with a history of acute coronary syndrome. Methods: the analysis is conducted on the basis of clinical outcomes of the PROVE-IT study. We conducted a cost-effectiveness analysis, comparing high dose of atorvastatin (80 mg/die) versus usual-dose of pravastatin (40 mg/die) in the perspective of the Italian National Health Service. We identified and quantified medical costs: drug costs according to the Italian National Therapeutic Formulary and hospitalizations were quantified based on the Italian National Health Service tariffs (2008). Effects were measured in terms of morbidity reduction (number of deaths and frequency of hospitalizations). We considered an observation period of 24 months. The costs borne after the first 12 months were discounted using an annual rate of 3%. We conducted one and multi-way sensitivity analyses on unit cost and effectiveness. Results: the cost of pravastatin or atorvastatin therapy over the 2 years period amounted to approximately 664.684 millions euro and 909.006 euro per 1,000 patients respectively. Atorvastatin was more efficacious compared to pravastatin and the overall cost of care per 1,000 patients over 24 months of follow-up was estimated at 2.58 millions euro in the pravastatin and 2.57 millions euro in the atorvastatin group, resulting into a cost saving of about 11.000 euro. Discussion: this study demonstrates that high dose atorvastatin treatment leads to a reduction of direct costs for the National Health System. Atorvastatin therapy is dominant since it is both less costly and more effective than pravastatin. Results were sensitive to either clinical or economic variables.